2019
DOI: 10.1111/ajt.15550
|View full text |Cite
|
Sign up to set email alerts
|

A B cell–dependent pathway drives chronic lung allograft rejection after ischemia–reperfusion injury in mice

Abstract: Chronic lung allograft dysfunction (CLAD) limits long‐term survival after lung transplant (LT). Ischemia–reperfusion injury (IRI) promotes chronic rejection (CR) and CLAD, but the underlying mechanisms are not well understood. To examine mechanisms linking IRI to CR, a mouse orthotopic LT model using a minor alloantigen strain mismatch (C57BL/10 [B10, H‐2b] → C57BL/6 [B6, H‐2b]) and isograft controls (B6→B6) was used with antecedent minimal or prolonged graft storage. The latter resulted in IRI with subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 64 publications
(98 reference statements)
3
28
0
Order By: Relevance
“…Watanabe et al. have further illustrated within a murine model that depletion of CD20+ cells may reduce graft ischemia-reperfusion injury [35] .Though our study could not show direct benefit to allograft tolerance, it did illustrate that RTX can induce a significant reduction in IL-13 and MCP-1, both of which are cytokines associated with B-cells [ 36 , 37 ]. Both IL-13 and MCP-1 have been suggested to play a role in rejection with their involvement in cases of lung inflammation as well as bronchiolitis obliterans syndrome [38] , [39] , [40] , [41] .…”
Section: Discussionmentioning
confidence: 56%
“…Watanabe et al. have further illustrated within a murine model that depletion of CD20+ cells may reduce graft ischemia-reperfusion injury [35] .Though our study could not show direct benefit to allograft tolerance, it did illustrate that RTX can induce a significant reduction in IL-13 and MCP-1, both of which are cytokines associated with B-cells [ 36 , 37 ]. Both IL-13 and MCP-1 have been suggested to play a role in rejection with their involvement in cases of lung inflammation as well as bronchiolitis obliterans syndrome [38] , [39] , [40] , [41] .…”
Section: Discussionmentioning
confidence: 56%
“…In addition to macrophages, myeloid (neutrophils, eosinophils, mast cells, and dendritic cells) and lymphoid cells are also abundantly present within the various stages of AFE, and specifically B cell–dominant lymphoid follicles 36 are thought to be crucially important for the development of AFE 37 and can be considered to be a response to the recognition of donor antigens, as donor‐specific antibodies (DSA) are more frequently found in RAS 38,39 (Figure 2). Montero et al furthermore demonstrated that compared to idiopathic PPFE, all patients with a clinical RAS diagnosis showed some degree of intra‐alveolar fibrosis and elastosis, but also an increase in vascular lymphoplasmocytic inflammation with fibrointimal thickening was observed at the advancing edge of the fibrosis in RAS compared to idiopathic PPFE 40 …”
Section: Restrictive Allograft Syndromementioning
confidence: 99%
“…In addition to macrophages, myeloid (neutrophils, eosinophils, mast cells, and dendritic cells) and lymphoid cells are also abundantly present within the various stages of AFE, and specifically B cell-dominant lymphoid follicles 36 are thought to be crucially important for the development of AFE 37 and can be considered to be a response to the recognition of donor antigens, as donor-specific antibodies (DSA) are more frequently found in RAS 38,39 (Figure 2).…”
Section: Re S Tric Tive Allog R Af T Syndromementioning
confidence: 99%
“…Previous reports provided evidence showing ectopic lymphoid tissues in chronically rejected grafts in the heart and kidney play a role in generating local humoral alloimmune responses[ 72 ]. Moreover, in a recent study of mouse orthotopic lung transplantation, chronic rejection after ischemia-reperfusion injury showed an increase in B cells in TLS of the graft[ 78 ]. Thus, BALT may be associated with rejection after lung transplantation by inducing immune cells.…”
Section: Anatomical Changes In Transplanted Lungsmentioning
confidence: 99%